Change and continuity in Burundian divinatory healing. Issue 1 (2nd January 2018) - Ventevogel, Peter; Niyonkuru, Jérémie; Ndayisaba, Aline; Reis, Ria; de Jong, Joop T.V.M.
ABSTRACT: Traditional healing practices in Burundi are rarely documented within ethnographic literature; further, it is unknown how practices have changed in the last two decades. This paper analyses data based on interviews and observations with seven Burundian abapfumu (diviner-healers), and 14 focus group discussions with community members. The results show that the position of traditional healers towards tradition is ambivalent; giving less emphasis to the role of ancestor spirits causing and healing misfortune than in the past. Some of the interviewed healers belonged to the kubandwa cult that is found all over the African Great Lakes Area. In this adorcistic cult, afflicted persons are assisted to enter into a peaceful and accepting relation with the possessing spirit. More recently a novel healing technique ( gucekera ), has emerged, in which unknown spirits are aggressively driven out of the affected person. As elsewhere in Africa, the rise of exorcistic healing in Burundi may be a reaction to the breakdown of community structures resulting from the collective violence and mass displacements that occurred over the past decades. Further, the results show that Burundian healers have considerable flexibility in adapting to new circumstances and are attempting to create new 'niches' within a society that is profoundly changing.